Addressing mental health stigma: A pilot educational video intervention for caregivers to facilitate psychiatric consultation in inpatient pediatric care settings. (October 2019) - Talbot, Rachel; Malas, Nasuh
Mental health stigma continues to be a significant barrier for psychiatric care in youth. Parental misperceptions regarding mental health may interfere with their child's care and negatively influence their child's view of mental health. For some children, their first experience with psychiatry occurs during medical hospitalization when they are seen by the Pediatric Consultation-Liaison (C/L) Psychiatry Service. Despite this unique role, there is sparse research on how to address mental health stigma with patients and families within the context of Pediatric C/L Psychiatry. This study explores the use of a brief educational video with messages from the Pediatric C/L Psychiatry team, families who have accessed mental health consultation in the hospital, and brief video interactions between family and the C/L team, to address mental health stigma. Common misconceptions are addressed during the video with the intent of reducing negative parental perceptions relating to mental health care. Families are given a survey highlighting these concerns, prior to and after watching the video. Pre- and post-intervention responses were compared using paired sample's t-tests. Results indicated that the video did positively change parent's confidence that psychiatry can be helpful, reduced their preconceived stigma regarding confidentiality, while alleviating concerns regarding psychotropic medication use in youth. Use of an educational video may be feasible, time efficient, and effective at reducing parental mental health stigma.